Efficacy of a commercially available multi-herbal formulation in periodontal therapy - A Suchetha; Ashit G Bharwani (Wolters Kluwer Medknow Publications, 2013)
Objective: This prospective clinical trial was designed to evaluate the clinical effects of a commercially available powder (Periocare ® Gum massage powder), containing various herbal medicaments, in the reduction of plaque and gingival inflammation in subjects diagnosed with gingivitis. Materials and Methods: Seventy-five subjects diagnosed with chronic generalized gingivitis were selected and randomly divided into the following three groups: Group I - Scaling + Periocare ® Gum Massage powder, Group II - Periocare ® Gum Massage powder alone, and Group III - Scaling only. Clinical evaluation was done at baseline, 2 weeks, 4 weeks, and 6 weeks using gingival index, plaque index, and microbiological culturing of plaque samples. Results: Periocare ® Gum Massage (multi-herbal formulation) powder as an adjunct to mechanical therapy (scaling) showed significant clinical and microbiological improvement in the gingival index and plaque index scores as compared to other groups. Periocare ® Gum Massage powder as a monotherapy did not prove to be effective for plaque control. Conclusion: Periocare ® Gum Massage may be a useful herbal formulation for chemical plaque control and improvement in plaque scores and gingival status.